Fundamental J. Hajek lema for samples from finite population of vectors - Bikelis, Algimantas; Turkuvienė, Jurgita (Lietuvos matematikos rinkinys, 2004)
Paper deals with J. Hajek's lema for samples from finite population of vectors.
Keywords: series of independent random vectors; Hajek lema; simple random sample; Poisson sample